Cardiovascular health knowledge, attitude and practice among school-going adolescents and the availability of digital prerequisites for health education in Bhaktapur, Nepal - Dayana Shakya; Nawi Ng; Natalia Oli; Abhinav Vaidya; Alexandra Krettek (PLoS ONE, 2025)
Background In Nepal, the proportion of annual deaths from cardiovascular disease (CVD) increased from 12% in 1990 to 22% in 2021. Although CVD manifests in adulthood, exposure to risk factors begins early in life. In Nepal, a high prevalence of risk factors combined with limited knowledge about cardiovascular health warrants a life course approach. One strategy could be a digitalized health education targeted at adolescents to prevent future CVDs. Methods We conducted a cross-sectional survey to assess adolescents’ knowledge, attitude and practice (KAP) regarding cardiovascular health and explored possibilities for digital education. In total, 649 adolescents in grades 8–10 from two public and seven private schools in a semi-urban community of Nepal were surveyed. A self-administered questionnaire assessed KAP, digital prerequisites such as mobile phone use and internet availability at home, and gaming behaviors. Quantile regression was performed to assess the relationship among the variables. Results The median scores were 69.1% (Interquartile range/IQR 63.1%–74.4%) for knowledge about cardiovascular health, 77.9% (73.3%–82.3%) for attitude and 76.7% (72.2%–81.1%) for practice. Quantile regression showed that the knowledge score for grade 9 adolescents was 4.2 percentage point (pp) higher (p < 0.001) and grade 10 adolescents was 4.0pp higher (p < 0.001) than those in grade 8. Knowledge was 4.9pp higher (p < 0.001) for private than for public school adolescents. Attitude scores were 2.0pp higher (p = 0.001) for girls than for boys and 1.7pp higher (p = 0.008) for private than for public school adolescents. For practice, boys scored 2.2pp higher (p < 0.001) than girls and private school adolescents scored 2.5pp higher (p < 0.001) than public. Furthermore, 98.6% of adolescents had smartphone access, 91.5% had internet access and 68.0% played mobile games. Conclusion Adolescents have lower knowledge than attitude and practice regarding cardiovascular health. This combined with high digital access provides opportunities for digital health education, especially in public schools.